Magnetically-guided hydrogel capsule motors produced via ultrasound assisted hydrodynamic electrospray ionization jetting - Rutkowski, Sven; Si, Tieyan; Gai, Meiyu; Sun, Mengmeng; Frueh, Johannes; He, Qiang (Journal of colloid and interface science, 2019)
[Display omitted] Hydrogel capsules are a potential candidate for drug delivery and an interesting alternative to polyelectrolyte multilayer capsules which are under investigation since 20 years. Recently introduced polyelectrolyte complex capsules produced by spraying are non-biodegradable and not biocompatible, which limits their practical application, while biodegradable alginate capsules require complex coaxial electrospray ionization jetting. In this work, biodegradable alginate capsules cross-linked by calcium are successfully produced by hydrodynamic electrospray ionization jetting with the assistance of low frequency ultrasound. The size and shape of most capsules show significant differences with respect to different spraying distance, spraying mode, electrode shape and spraying concentration. Capsules in the shape of vase, mushrooms and spheres were successfully produced. Average capsule size can be adjusted from 10 μm to 2 mm. These capsules are used to encapsulate a model drug. Encapsulated paramagnetic particles enable defined directional motion under the propulsion of a rotating magnetic field, while model drugs can be released by ultrasound.